Evaluasi Penyimpangan Lintasan Pengeboran Berarah Dan Pengaruhnya Terhadap Pembebanan Drill String pada Sumur “A-A” Lapangan "CPG - Avis Akbar; Sari Wulandari Hafsari; Lia Yunita (Jurnal Offshore: Oil, Production Facilities and Renewable Energy, 2024)
In drilling activities, wellbores inevitably experience deviation, commonly referred to as a crooked hole. If the deviation is significant, the loading on the drill string becomes one of the reasons why drilling does not go as planned and may even fail. The purpose of the research is to determine whether there is a deviation in the drilling path between the planned trajectory and the actual trajectory in well 'A-A' in the CPG field. By evaluating the drilling path deviation, it can be determined whether the load experienced by the drill string exceeds the predefined limits. The Minimum of Curvature method has the advantage of having minimal deviation and inclination, making it accurate with the plan. Therefore, this method is used to calculate the drilling path. Using the parameters of Measured Depth, Inclination, and Azimuth, the method will calculate the Radius Factor, Grid North, Grid East, Vertical Depth, and Vertical Section. The planned and actual data will then be compared to identify any deviation. Drill string load calculations will be performed if a deviation is found using the H. Rabia and Bill Mitchel equations to calculate Weight on Bit, Drag, Tension, Margin of Overpull, Torsion, and Buckling Load. The deviation results, such as at the Kick Off Point (KOP), show that in the plan, it is located at a depth of 1,378.02 Ft MD and 0.75 Ft Vsec, while in actual practice, it is at a depth of 1,275.65 Ft MD and -0.79 Ft Vsec. In Trajectory #1 for Surface Casing in the plan, it is at a depth of 2,067.03 Ft MD and 89.21 Ft Vsec, while in actual practice, it is at a depth of 1,963.68 Ft MD and 80.42 Ft Vsec. In Trajectory #2, the plan is at a depth of 3,724.52 Ft MD and 402.38 Ft Vsec, while in actual practice, it is at 3,695.72 Ft MD and 385.71 Ft Vsec.